Pengaruh Kecukupan Modal, Likuiditas, Risiko Kredit, Dan Efisiensi Operasional Terhadap Profitabilitas Perusahaan - Salamah, Umi; Puspitasari, Elen (Gorontalo Accounting Journal, 2024)
The aim of this study is to determine the impact of capital adequacy ratio, liquidity, credit risk, and operational efficiency on profitability in conventional banking companies listed on the Indonesia Stock Exchange for the period 2019-2022. This research employs purposive sampling technique, utilized to gather secondary data from the IDX website, with a sample of 27 banking companies processed using SPSS 26 software. The findings of this study demonstrate that the tested analysis results show that simultaneously, the Capital Adequacy Ratio, Credit Risk, Liquidity, and Operational Efficiency ratios influence Profitability. Partially, the Capital Adequacy Ratio, Credit Risk, and Liquidity affect Profitability (Return on Asset-Return on Equity). Meanwhile, Operational Efficiency only affects Return on Asset but not Return on Equity.